Perubahan Mutu Gudeg Kaleng “Bu Tjitro” Selama Penyimpanan - Asep Nurhikmat; Bandul Suratmo; Nursigit Bintoro; Suharwadji Sentana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2015)
Gudeg is a traditional food from Yogyakarta with a short shelf life. To extend the shelf-life, gudeg packed with cans. Research on quality changes during storage of canned gudeg had been done. The study was conducted in order to determine quality changes that occur in canned gudeg during the storage period. Canned gudeg material consisted of gudeg jackfruit, eggs, chicken, krecek and tolo beans with size cans of 72.63 x 53.04 mm (Ø x h). Observations canned gudeg quality performed for 18 months with 3-month interval includes the analysis of physical, chemical, microbiological and organoleptic. The results showed that there were quality changes, including 0.6 points of pH, 36% of soluble protein, 20.15 ppm of aluminum content, 0.06 mg malonaldehyde/kg for TBA value, 5.1 points color brightness and 2 CFU/g total microbial, as well as decline in15.77 ppm sulfur and organoleptic quality parameters. Canned gudeg hold for 15 months with 68.49% of water contents; of 1.56% ash content; 8.40% of protein content; 12.74% of fat content and 5.60% of fiber content.ABSTRAKGudeg adalah makanan tradisional dari Yogyakarta dengan masa simpan pendek. Untuk memperpanjang masa simpannya, gudeg dikemas dengan kaleng. Penelitian tentang perubahan mutu gudeg kaleng selama penyimpanan telah dilakukan. Penelitian dilakukan dengan tujuan untuk mengetahui perubahan mutu yang terjadi pada gudeg kaleng selama masa penyimpanan. Bahan gudeg yang dikalengkan terdiri dari gudeg nangka, telur, daging ayam, krecek dan kacang tolo dengan kemasan kaleng ukuran 72,63 x 53,04 mm (Ø x h). Pengamatan mutu gudeg kaleng dilakukan selama 18 bulan dengan interval 3 bulan meliputi analisis fisika, kimia, mikrobiologi, dan organoleptik. Penelitian menghasilkan perubahan yang terjadi pada gudeg kaleng selama penyimpanan antara lain kenaikan pH 0,6 poin, protein terlarut 0,73%, kadar aluminium 20,15 ppm, nilai TBA 0,06 mg malonaldehid/kg, kecerahan warna 5,1 poin dan total mikroba 2 CFU/g. Selama penyimpanan penurunan sulfur 15,77 ppm dan penurunan parameter mutu organoleptik. Gudeg kaleng tahan selama 15 bulan dengan kadar air 68,49%; kadar abu 1,56%; kadar protein 8,40%; kadar lemak 12,74%, dan kadar serat 5,60%.